Rancang Bangun Aplikasi Profil Teknik Informatika Politeknik Kampar Menggunakan Sistem Operasi Android - Fenty Oktorina (Politeknik Kampar, 2018)
In the digital era, people use smartphones almost all the time, showing that smartphones have become a part of human life. This phenomenon is used by many parties to promote quickly and practically. Likewise, the Informatics Engineering Study Program (PS-TIF) is considered necessary to create a profile that can be accessed via smartphones that use the Android operating system